1994
DOI: 10.1042/bj3010777
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-stable sialidase activity in human leucocytes: substrate specificity, inhibitor susceptibility, detergent requirements and subcellular localization

Abstract: Human leucocytes contain a freeze-stable sialidase (neuraminidase; EC 3.2.1.18) activity in addition to the better-characterized lysosomal freeze-labile enzyme. In order to discriminate between the sialidase activities detected with the synthetic fluorimetric substrate 4-methylumbelliferyl-alpha-D-N-acetylneuraminic acid (MU-Neu5Ac), different tritiated sialoglycoconjugate substrates were prepared. Using this sensitive radioactive assay system, leucocyte sialidase activity towards glycoproteins was shown to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…With improvements over the last 20 years in the techniques to prepare leukodepleted cellular blood components, it has been possible to study the potential damage that could be wrought by the many degradative enzymes that are released by the progressive lysis of leukocytes on storage. These are mainly proteases that are responsible for hemolysis (13, 15, 22), because stored RBCs lack the protective effect of plasma which contains an array of antiproteases (33) and sialidases that have been identified in lytic products of leukocytes (9–11, 14) and to which the cause of the premature senescence of stored RBCs and the loss of viability of these cells could be attributed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With improvements over the last 20 years in the techniques to prepare leukodepleted cellular blood components, it has been possible to study the potential damage that could be wrought by the many degradative enzymes that are released by the progressive lysis of leukocytes on storage. These are mainly proteases that are responsible for hemolysis (13, 15, 22), because stored RBCs lack the protective effect of plasma which contains an array of antiproteases (33) and sialidases that have been identified in lytic products of leukocytes (9–11, 14) and to which the cause of the premature senescence of stored RBCs and the loss of viability of these cells could be attributed.…”
Section: Discussionmentioning
confidence: 99%
“…First, apoptosis occurs in white cells within the first 48–72 h of storage, leading to the formation of membrane fragments that adhere to RBCs and initiate erythrophagocytosis (9–11). Second, by the same mechanism, active enzymes, including neuraminidases, are released in the storage medium (12–15). Third, many authors have reported the advantages of leukodepletion prior to storage of RBCs in preventing the deleterious effects observed with nonleukodepleted RBC transfusion (see refs.…”
mentioning
confidence: 99%
“…7,15 While the escalation in neuraminidase activity observed in sepsis may be attributed to the presence of bacteria in the circulation, 36 neuraminidases released from host cells including platelets, leukocytes, and erythrocytes per se may, in addition, contribute to this effect. 15,34,37 Mounting evidence suggests that increased PS externalization, triggered by a host of bacterial components such as peptidoglycan, lipopeptides, sphingomyelinase, Pseudomonas aeruginosa pyocyanin, and α-hemolysin, shortens erythrocyte lifespan, thus, contributing to sepsis-associated anemia. 17,20,22,29,38 Along these lines, it may be conjectured that enhanced neuraminidase activity in septic patients contributes to aggravated eryptosis and anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, both increased plasma levels of SA and blood neuraminidase activity have been reported in septic patients . While the escalation in neuraminidase activity observed in sepsis may be attributed to the presence of bacteria in the circulation, neuraminidases released from host cells including platelets, leukocytes, and erythrocytes per se may, in addition, contribute to this effect . Mounting evidence suggests that increased PS externalization, triggered by a host of bacterial components such as peptidoglycan, lipopeptides, sphingomyelinase, Pseudomonas aeruginosa pyocyanin, and α‐hemolysin, shortens erythrocyte lifespan, thus, contributing to sepsis‐associated anemia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation